The effect of cosmos caudatus on chronic repetitive forced swimming stress / Mohd Hadzrul Hisham Abdul Manaf - Abdul Manaf, Mohd Hadzrul Hisham (2016)
Chronic stress has been identified as the major pathophysiological etiology for numerous of diseases. One of the underlying detrimental mechanism induced by stress is caused by oxidative stress. The redox imbalanced due to oxidative stress is found to be reversible by the action of antioxidant. The present study focused on the effect of Cosmos caudatus (C. caudatus) towards biological stress markers. Male Sprague-Dawley rats were randomly divided into 5 groups, treated with methanolic extract of C. caudatus leaves (100 & 200 mg/kg), quercetin (100 & 200 mg/kg) and saline (control) respectively for 21 days prior and throughout the 13 days of experiment. The rats were then subjected to forced swimming stress and bloods were withdrawn at 6 different days (Basal, Day 1 and every 2 days continuously). The blood analysis revealed that treatment with C. caudatus able to reduce plasma corticosterone level significantly (p<0.005) compared to the control group, reduced plasma malondialdehyde level (p<0.005) and increased plasma total antioxidant capacity level (p<0.005) in the rats following stress exposure. C. caudatus was also found to have a preservation effect on the plasma dehydroepiandrosterone-sulphate level by inhibiting the fluctuation (increment and reduction) in its level following stress exposure. Based on these observations, it is concluded that C. caudatus act as an anti-stress agent through the action of antioxidant activities in modulating stress response mechanisms and serve as a protective agent towards the pathological effect induced by stress.